Excavating the Memory Palace: An Account of the Disappearance of Mnemonic Imagery from English Rhetoric, 1550–1650. Issue 2 (3rd April 2017) - Long, Seth
Abstract : In the sixteenth and seventeenth centuries, the visual precepts of rhetoric's fourth canon found themselves at odds with the iconoclasm of England's Protestant elite. Under this negative influence, mnemonic imagery disappeared from rhetorical theory. Interest in the fourth canon declined, replaced with a Ramist conception of memory grounded in abstract (and imageless) order. A general outline of this history has been offered by several scholars—most notably, Frances Yates—but new bibliographic data along with recently digitized archives can verify its accuracy. Print, written culture, or "modernist" ideologies alone cannot explain the historical marginalization of the canon of memory.